Seroprevalence of hepatitis B virus and hepatitis C virus co-infection in human immunodeficiency virus infected patients at a tertiary care hospital in South India - Kalyani, C. Siva; Lakshmi, N.; Lakshmi, Koripella Rama; Kumar, V. Ashok; Cheemala, Sulakshana Sony (International Journal of Research in Medical Sciences, 2017)
Background: About one third of human immunodeficiency virus (HIV) infected patients are co infected with either hepatitis B virus (HBV) or hepatitis C virus (HCV) as the three viruses have similar routes of transmission that is through transfusion of blood and blood products, sharing of needles to inject drugs and unprotected sexual activity. The survival of HIV infected patients has been markedly improved with highly active antiretroviral therapy (HAART). However several studies showed that the liver diseases caused by HBV or HCV have emerged as one of the leading causes of non AIDS related deaths in HIV patients. The objective of this work was to study the prevalence of HBV & HCV co-infection in HIV infected patients at a Tertiary care centre in South India. Methods: The study group includes 100 HIV seropositive individuals confirmed by three rapid tests as per NACO (National AIDS Control Organization) guidelines in ICTC (Integrated Counseling and Testing Centre), Department of Microbiology, Andhra Medical College, Visakhapatnam, Andhra Pradesh, India. Age and sex matched 100 HIV seronegative individuals were also included in the study as controls. Both the groups were screened for detection of HBV and HCV markers by one rapid test and a solid phase enzyme linked immunosorbent assay (sandwich ELISA). Results: Out of 100 HIV positive patients in the study group 12(12%) were co infected with HBV and 2(2%) were co infected with HCV. Out of 12 HIV and HBV co infected patients 7(58.3%) were females and 5(41.7%) were males. The HIV &HCV co infected patients were both females. Co infection of HBV & HCV with HIV was found to be 0(0%). Co infection was most commonly seen in the age group 31-40 years followed by 21 – 39 years. In the control group out of 100 HIV negative individuals, 1(1%) was infected with HBV infection. Conclusions: The routine screening of HBV and HCV should be mandatory for HIV infected patients, as there is more chance of co infection with these Hepatitis viruses due to enhanced immunodeficiency by HIV and similar routes of transmission. Clear National policies should be established which should include clear economic and health care strategies to improve quality of living conditions, education and easy access to health care facilities.